2016
DOI: 10.1038/srep25400
|View full text |Cite
|
Sign up to set email alerts
|

Ultrapure laser-synthesized Si-based nanomaterials for biomedical applications: in vivo assessment of safety and biodistribution

Abstract: Si/SiOx nanoparticles (NPs) produced by laser ablation in deionized water or aqueous biocompatible solutions present a novel extremely promising object for biomedical applications, but the interaction of these NPs with biological systems has not yet been systematically examined. Here, we present the first comprehensive study of biodistribution, biodegradability and toxicity of laser-synthesized Si-SiOx nanoparticles using a small animal model. Despite a relatively high dose of Si-NPs (20 mg/kg) administered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 69 publications
3
110
0
Order By: Relevance
“…As an example, some previous studies used designed SERS probes based on silica (SiO 2 )‐coated plasmonic structures, including gold nanorods and nanostars , to improve the biocompatibility and efficiency of SERS probes. The inclusion of nonoxidized crystalline silicon (Si) fraction into composition of SERS probes is expected to further improve the biocompatibility of these probes, as Si is one of the essential materials in biological systems, which does not provoke any toxic effects even under massive injection in vitro or in vivo . In addition, in contrast to silica, silicon can provide a distinct Raman scattering peak around 520/cm, which was clearly visible in our tests (Figure (B)).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…As an example, some previous studies used designed SERS probes based on silica (SiO 2 )‐coated plasmonic structures, including gold nanorods and nanostars , to improve the biocompatibility and efficiency of SERS probes. The inclusion of nonoxidized crystalline silicon (Si) fraction into composition of SERS probes is expected to further improve the biocompatibility of these probes, as Si is one of the essential materials in biological systems, which does not provoke any toxic effects even under massive injection in vitro or in vivo . In addition, in contrast to silica, silicon can provide a distinct Raman scattering peak around 520/cm, which was clearly visible in our tests (Figure (B)).…”
Section: Resultsmentioning
confidence: 78%
“…Crystalline silicon (Si) is a prominent example of such material, which is one of the essential elements in live organism and is present in many biological tissues in the form of orthosilicate (SiO 4 4− ) . We recently showed that contamination‐free laser‐synthesized Si NPs are not only well compatible with biological systems in vitro and in vivo , but are also biodegradable as they decay in aqueous environment into orthosilicic acid Si(OH) 4 and excrete from biological systems without any harmful effects . We envision that the coating of plasmon‐supporting SERS probes by Si shell could improve the compatibility of these probes with biological systems and bring novel functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Making possible fast production of bare (uncovered) NPs in colloidal state with almost any composition, pulsed laser ablation in liquids [12][13][14][15][16][17] (PLAL) provides one of best alternatives to satisfy the above-stated demands. As an example, we recently showed that the technique of femtosecond laser ablation in liquids can be used for the fabrication of a variety of ultrapure, biologically-friendly nanomaterials, including gold NPs [16,[18][19][20][21][22], titanium nitride (TiN) NPs [23], silicon NPs [24][25][26][27] and organic polymer NPs [28]. In many cases, such nanoparticles can provide superior properties for catalytic [20], energy and biomedical [29,30] applications, compared to nanomaterials synthesized by conventional chemical methods, and other methods.…”
Section: Sm Oxide Powder and Preparation Of Target For Ablationmentioning
confidence: 99%
“…This method renders possible an atural production of nanoclustersduring the interaction of intense laser radiation with at arget, [1][2][3][4][5] which can then form either an anostructured film (when ablated in gasses) [5][6][7][8][9][10] or colloidal nanoparticle solutions (when ablated in liquids). [16][17][18][19][20] Furthermore, bare (ligand-free) surfaceo fl aser-synthesized nanomaterials can have unique properties (e.g.,p articulars urface chemistry [24] and reactivity [25] ), which makes them extremely promising for various applications, including cancer theranostics, [26,27] neurology, [28] and biofuel cells. [16][17][18][19][20] Furthermore, bare (ligand-free) surfaceo fl aser-synthesized nanomaterials can have unique properties (e.g.,p articulars urface chemistry [24] and reactivity [25] ), which makes them extremely promising for various applications, including cancer theranostics, [26,27] neurology, [28] and biofuel cells.…”
Section: Introductionmentioning
confidence: 99%